The Impact of Using an Orientation program Based on English Teachers’ Self-assessment and Reflection on Students’ Learning Behaviors from the Teachers’ Perspectives - Jabber, Amal; Al-Shara’h, Nayel (DIRASAT: EDUCATIONAL SCIENCES, 2016)
This study investigated the impact of using an orientation program based on English language teachers’ self-assessment and reflection on students’ learning behaviors from the teachers’ perspectives. The subjects of the study were 26 English language teachers. The study was conducted by using a questionnaire that consisted of nine categories related to students’ learning behaviors. The results revealed that there was an effect of English teachers’ use of the orientation program on the enhancement of students’ learning behaviors. It is recommended that researchers conduct more educational research on teachers’ self-assessment and reflection techniques. Also it is recommended to employ the proposed orientation program and similar ones based on teachers’ self-assessment and reflection in training and preparing pre-service and in-service English teachers.